Collapse Mechanism and Full-Range Analysis of Overturning Failure of Continuous Girder Bridges - Taiyu Song; Qinger Deng; Guoping Li (Advances in Materials Science and Engineering)
In recent years, failings of girders due to overturning in continuous girder bridges have repeatedly occurred in China. To investigate the overturning collapse mechanism and also to evaluate the rationality of anti-overturning design method using beam element models that are commonly adopted in practical design, detailed 3D finite solid element models of a typical single-column pier three-span continuous box girder bridge were built and a full-range numerical analysis of the models was conducted. The solid models included the prestressing effect and diaphragms. Both boundary and geometric nonlinearities were taken into consideration. Bearings were modeled considering the actual construction and dimensions of pot rubber bearings, the material characteristics and boundary conditions of rubber pads, and the contact properties between each part of the bearings. The analysis results revealed that the behavior of the bridge approached the nonlinear state at the onset of first bearing disengagement; the rotation (overturning) mechanism of the girder was gradually transitioned from deformable-body rotation to rigid-body rotation; all the end and middle bearings had been disengaged totally or locally at ultimate overturning failure. The analysis results also showed that bearing disengagements would lead to the ineffectiveness of the constraint in the transverse direction, which significantly reduced the overturning ultimate load and structural ductility before the final collapse. Prior to the first bearing disengagement, the vertical reactions calculated from the beam model were in good agreement with those from the solid model, while the transverse reactions were not. The behaviors were inaccurate after bearing disengagement in the beam models in which the movement of the rotation axis and transition of rotation mechanism failed to be realized. Reliable transverse stoppers and tensile anchors at bearing sections were recommended to efficiently improve anti-overturning stability and ductility in practical design.